Effects of Pre-Injury Anti-Platelet Agents on Short-Term Outcome of Patients with Mild Traumatic Brain Injury: A Cohort Study - Farsi, Davood (Bull Emerg Trauma, 2017)
OBJECTIVE: To determine the effects of pre-injury consumption of anti-platelet agents on the 30-day outcomes of patients with mild traumatic brain injury (TBI). METHODS: This prospective cohort study was conducted at three general hospitals in Tehran, Iran between July 2013 and July 2014. The study population included all patients with mild TBI aged over 18 years that medicated with aspirin or clopidogrel before occurring trauma. Within hospitalization, all patients were assessed with respect to in-hospital conditions especially complications and adverse events. After discharge, the individuals were followed for 30 days by telephone to assess mortality and disability using the Glasgow outcome scale (GOS). RESULTS: Of 1140 patients with mild TBI, only 135 had previously received aspirin and/or clopidogrel. The mean age was dramatically higher in those who were taking aspirin or clopidogrel (p<0.001). The patients with previously use of anti-platelets were more transferred by ambulance when compared to another group (p=0.006). The patients on anti-platelets had significantly lower GCS on admission when compared to others (p<0.001). Length of hospitalization was significantly longer in those receiving anti-platelets (p=0.003). In follow-up, 30-day mortality and disability was revealed in 2.8% of patients that received only aspirin and 7.5% in aspirin with clopidogrel and in 1.6 % of those who did not receive drugs without any significant difference between aspirin and control group (p=0.208) and significant difference in aspirin with clopidogrel group (p<0.001).   CONCLUSION: The premedication by anti-platelets (aspirin and/or clopidogrel) in patients with mild TBI leads to prolonged hospital stay, and increase rate of disability. Age and on admission GCS are the independent risk factors for predicting the outcome in patients with mild TBI receiving anti-platelet agents.